Toothpick perforation of the cecum in a child mimicking acute appendicitis - Rami Al-Addasi; Raed Al-Taher; M.S. Elmuhtaseb; Walid Al-Natsheh; Dania Qarkash; Hams Al-Khlifat; Fatima Al-Soub; Haitham Al Zoubi (Elsevier, 2021)
We present a case of cecal perforation secondary to a toothpick ingestion, which was not diagnosed by history, physical examination or imaging techniques, and was diagnosed intraoperatively during a laparoscopic appendectomy.